EFFECT OF SURFACE TREATMENT ON FLEXURAL STRENGTH AND SUBCRITICAL CRACK GROWTH OF LITHIUM DISILICATE: AN IN VITRO STUDY - DE CARVALHO, Ronaldo Luís Almeida; Miranda, Jean Soares; Ramos, Nathália de Carvalho; Weitzel, Isabela Sandim Souza Leite; Amaral, Marina; Kimpara, Estevão Tomomitsu [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
Alternative surface treatments have been proposed for the cementation of lithium disilicate ceramics aiming to improve adhesive and flexural strength under fatigue. This study aimed to evaluate the slow crack growth (SCG) parameters of the lithium disilicate ceramic after hydrofluoric acid (HF) etching or air abrasion (AB) as surface treatments. Ceramic discs were treated with HF (5%, 20 s) or AB (30 µm silica-modified alumina particles, 2.8 bar, 10 mm distance, 15 s), and received a layer of resin cement. The surface roughness after surface treatment was evaluated (n = 5). Samples were tested in a piston-on-three-ball assembly to evaluate the flexural strength (n = 20), inert strength (n = 25), and to determine SCG parameters n and D (n = 35). The highest roughness (p < 0.01) was observed in the AB group, with the highest reliability according to the Weibull analysis, but the lowest SCG susceptibility. Flexural (p = 0.03) and inert strength (p < 0.01) were the greatest in the HF group. Despite exhibiting lower strength than 5% HF, air abrasion may be an alternative for the surface treatment of lithium disilicate surfaces, indicating the best prognosis over time.
Keywords: Ceramic; Fatigue; Flexural strength; Surface properties